Technological innovation and sustainable intensification: Highlights, lessons learned, and priorities for One CGIAR - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2021)
What are the key drivers of change in agrifood systems? What challenges do these drivers present to achievement of sustainable food and nutrition security at global, regional, and national scales? How can agricultural technologies, natural resource management practices, and investment in infrastructure address these challenges in ways that manage trade-offs, protect natural capital, and sustain the provision of ecosystem services? PIM researchers analyzed the consequences of a number of key drivers for the future development of food systems. The primary focus has been on climate change, population and income growth, food prices, and their combined effects on dietary preferences, health, and the environment, as well as on the role of changing technology and responses to investments in key components of the food system. A body of work comprised of ground-breaking original research and review studies was made possible by the successful building of a community of practice on foresight that brought together researchers across CGIAR with collaborators from academia and centers of excellence all over the world.